(untitled) (Journal of Pathology of Nepal, 2021)
Background: Papillary squamotransitional cell carcinoma is a histopathological subcategory of squamous cell carcinoma of the uterine cervix that often resembles transitional cell carcinoma of the urinary tract. Histologically, it can be misdiagnosed as transitional cell carcinoma or other papillary lesions of the cervix. Stromal invasion on biopsy is difficult to diagnose due to the exophytic papillary growth of the tumor. It also has a propensity for local recurrence and late metastasis. The study is performed to diagnose and categorize this uncommon variant of carcinoma cervix. Materials and Methods: Eighteen cases of Papillary squamotransitional cell carcinoma were diagnosed on a punch biopsy specimen on routine hematoxylin and eosin-stained sections. The tumors were categorized into three groups according to the percentage of squamous and transitional components. Further, immunohistochemical evaluation for cytokeratin7 and cytokeratin20 was done. Results: The mean age of the patients was 51.61 years (range 37-62 years). The most common clinical presentation was postmenopausal bleeding. All the cases showed papillary architecture with fibrovascular cores. The papillae were lined by three cell types: clear, intermediate, and basaloid. Stromal invasion was seen in all the cases. All the cases showed positive immunostaining for cytokeratin7 and negative immunostaining for cytokeratin20. Conclusions: Papillary squamotransitional cell carcinoma deserves accurate pre-operative biopsy diagnosis due to the risk of misdiagnosis as benign papillary or malignant transitional lesions. Immunohistochemistry plays an important role in the diagnosis of these tumors and is recommended in every case. Late recurrence and metastasis warrants a longer duration of follow up.